2022
DOI: 10.3390/toxics10050267
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of Exposure to Urban Pollutants and Oxidative Stress during the COVID-19 Lockdown in Rome Residents

Abstract: Background: The objective of this study is to evaluate the effects of traffic on human health comparing biomonitoring data measured during the COVID-19 lockdown, when restrictions led to a 40% reduction in airborne benzene in Rome and a 36% reduction in road traffic, to the same parameters measured in 2021. Methods: Biomonitoring was performed on 49 volunteers, determining the urinary metabolites of the most abundant traffic pollutants, such as benzene and PAHs, and oxidative stress biomarkers by HPLC/MS-MS, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…On the other hand, oxidative stress is a risk factor for COVID-19 infection [ 40 ]. However, some authors have shown that oxidative stress was reduced due to confinement, as exposure to urban pollutants was reduced [ 41 ]. Therefore, the lack of difference in changes between both groups could be explained by the decrease in external oxidants, such as those related to pollution.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, oxidative stress is a risk factor for COVID-19 infection [ 40 ]. However, some authors have shown that oxidative stress was reduced due to confinement, as exposure to urban pollutants was reduced [ 41 ]. Therefore, the lack of difference in changes between both groups could be explained by the decrease in external oxidants, such as those related to pollution.…”
Section: Discussionmentioning
confidence: 99%
“…HBM can also be used to assess the impact of management measures taken to reduce external exposures. In their study, Buonaurio et al (2022) [ 15 ] evaluated the effects of traffic on human health comparing biomonitoring data measured during the COVID-19 lockdown, when restrictions led to a 40% reduction in airborne benzene in Rome and a 36% reduction in road traffic, to the same parameters measured in 2021. Their results confirmed a decrease in succinic acid, a product of the Krebs cycle promoting inflammation.…”
mentioning
confidence: 99%